Political Will Di Dalam Undang Undang Republik Indonesia No 6 Tahun 2014 Tentang Desa - Kurniawan, Mahda Reza (POLITEA, 2019)
People in a country, of course, have the customs and culture of each. This custom was born and developed from the behavior that was sustained in a relatively long time on the initiative of the party who first set. In its development, the behavior is then followed by several individuals in the social space to foster a culture-customs and traditions. In the era of globalization, where cultures, customs or habits that may be opposed to the state ideology enter freely, this is where the state is present to protect these customs along with the actors who have been implementing them. The presence of the state in the government's efforts to create good governance and political will is implicit and explicit in the Law of the Republic of Indonesia No. 6 of 2014 concerning Villages.The article examines and discusses and examines the law on village number 6 in 2014 with paradigm, socio-political-anthropological. Studies and studies are carried out using the literature study method in the law with guidelines and a blend of Political, Social and Anthropological theories.In the discussion and conclusion, it is explained and discussed that in the village law explicitly and implicitly indeed shows that the government has a good faith in organizing the country in accordance with the goals and vision of the state mission, in the context of village laws.